1996
DOI: 10.1084/jem.183.6.2605
|View full text |Cite
|
Sign up to set email alerts
|

Experimental granulomatous colitis in mice is abrogated by induction of TGF-beta-mediated oral tolerance.

Abstract: SummaryIn previous studies we showed that a chronic colitis associated with a Thl T cell response can be induced by the rectal administration of the haptenizing reagent 2,4,6-trinitrobenzene sulfonic acid (TNBS). We report here that oral administration of haptenized colonic proteins (HCP) before rectal administration of TNBS effectively suppresses the ability of the latter to induce colitis. This suppression (oral tolerance) appears to be due to the generation ofmucosal T cells producing TGF-[3 and Th2-type cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
271
0
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(289 citation statements)
references
References 31 publications
12
271
0
6
Order By: Relevance
“…TNBS-driven colitis is initiated by intrarectal instillation of a solution of ethanol, which breaks the mucosal barrier, with TNBS, which haptenizes autologous colonic or microflora proteins, leading to Th1 and Th17 responses (64). Despite the fact that the TNBS colitis model was traditionally considered T cell-dependent (65), studies have demonstrated that it can develop in the absence of adaptive immunity (66). Chemical haptens are sensitizers with a high ability to elicit DC migration from the sites of sensitization to draining LNs to present antigens and activate immune responses (67).…”
Section: Discussionmentioning
confidence: 99%
“…TNBS-driven colitis is initiated by intrarectal instillation of a solution of ethanol, which breaks the mucosal barrier, with TNBS, which haptenizes autologous colonic or microflora proteins, leading to Th1 and Th17 responses (64). Despite the fact that the TNBS colitis model was traditionally considered T cell-dependent (65), studies have demonstrated that it can develop in the absence of adaptive immunity (66). Chemical haptens are sensitizers with a high ability to elicit DC migration from the sites of sensitization to draining LNs to present antigens and activate immune responses (67).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Neurath et al [21] showed that these transferred T cells migrate to the recipient's colon, which results in lymphoid infiltrates in the colon. However, from the latter study it is not clear if T cells exclusively migrate to the colon, nor if other inflammatory cells migrate to the colon upon T cell transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Such T cells have a unique cytokine production profile in that they produce high levels of TGF-␤ without necessarily producing either Th1 or Th2 cytokines; therefore, they have been dubbed Th3 T cells (12). Th3 cells producing TGF-␤ have also been shown to occur in experimental models of colitis or diabetes or in HgCl 2 -induced autoimmune disease, and in these instances it is thought that such T cells play an important role in disease prevention or cure (13)(14)(15)(16). Recently, another type of regulatory T cell has been identified (in both mice and humans) that may be related to the aforementioned Th3 T cell.…”
mentioning
confidence: 99%